IMPROVING THE ASSESSMENT AND MANAGEMENT OF ECONOMIC EFFICIENCY OF INVESTMENT PROJECTS IN THE CONSTRUCTION SECTOR (International Congress on Economics, Management and Business Studies, 2026)
Investment projects in the construction sector play a crucial role in economic growth, infrastructure development, and social welfare. However, the high capital intensity, long project cycles, and exposure to various risks make the evaluation and management of their economic efficiency particularly complex. This paper examines modern approaches to assessing and managing the economic efficiency of construction investment projects and proposes improved economic mechanisms. Special attention is given to financial evaluation methods, risk management tools, and digital technologies such as Building Information Modeling. The study identifies key challenges in current practices and provides recommendations for enhancing decision-making processes. The results contribute to improving the sustainability and profitability of construction investments.
Keywords: Construction investment, economic efficiency, project evaluation, risk management, BIM, cost-benefit analysis